READING THE ARGUMENT AS ASSESSMENT PROCESS INDONESIAN OPINION TEXT - Sri Kusuma Winahyu, Endry Boeriswati, Fathiaty Murtadho (International Journal of Advanced Science and Technology, 2020)
The development of opinion text assessment at this time was very rapid until a computer-based assessment emerged. In this kind of assessment, the emphasis is on seeing the tendency of the number of positive and negative words in the text. In fact, the main element of opinion text is the argument. This research seeks to deepen the linguistic process in opinion assessment before it can later proceed towards computer-based assessment. The analysis offered is the use of the theory of reading evaluation which is applied with the Rhetorical Structure Theory (RST) and Toulmin’s argument theory. These steps are able to make the findings of the author’s argument more accurate than just looking for positive and negative words in the text.